Malnutrition and Disability: The Indian Scenario (International Journal of Food and Nutritional Sciences, 2022)
India is the world's second most populated country. Both malnutrition and disability have affected its people on a large scale. In this paper the researcher will explain the relation between malnutrition and disability. The researcher will also highlight the situation of malnutrition in India. This paper will also throw some light on how malnutrition is aggravating disability in India. this study will also explore the measures taken to overcome malnutrition in India. The researcher will also give some suggestions to deal with the problem of malnutrition in India.